A functional analysis of inflorescence architecture in Musa L. (Musaceae) - Turner, David W.; Gibbs, D. Jane; Ocimati, Walter; Blomme, Guy (Wiley, 2024)
Inflorescence architecture underpins sexual reproduction in wild Musa species and productivity in edible banana cultivars. In a functional analysis, we identified the apical inflorescence and lateral ‘cushion’ meristems and the change in flower type as the three primary components that generate inflorescence architecture. Five genotypes of two clone sets of edible plantains ( Musa AAB) were grown for four generations along an elevation gradient (1100–2200 m, 16°C–24°C) straddling the equator in the humid highlands of East Africa. The data consisted of reproductive peduncle length at harvest ( Pr ), fruit per hand ( Fh ) and hands per bunch ( Hb ). The activity of the apical inflorescence meristem drives peduncle length and generates lateral ‘cushion’ meristems which determine Fh . However, Hb is determined by a change in flower type—from fruit forming to non‐fruit forming. Site temperature affected Hb more than Fh , while the development of the genet (rhizome) changed the allocation of resources between Hb and Fh , independently of the effect of site temperature. Clone sets differed in their response to genet development. Cooler temperatures reduced the number of fruit‐forming flowers in an inflorescence and changed the balance away from female towards male flowers. In banana breeding schemes, manipulating inflorescence components independently raises options for producing genotypes better suited to markets, environments and cultural practices.